Microbiology : (McGraw-Hill, 2009)
ppropriate for the non-major/allied health student, this authoritative text carefully explains the fundamentals of microbiology, providing a general overview of the principles followed by more detailed explanations. With its clear and concise writing style, Microbiology: A Human Perspective offers modern coverage on such topics as genomics, biofilms, and quorum sensing. A body systems approach is used in the coverage of diseases.